Professional SQL server 2005 administration - Knight, Brian, 1976- (Wrox professional guides., 2007)
SQL Server 2005 is the largest leap forward for SQL Server since its inception. With this update comes new features that will challenge even the most experienced SQL Server DBAs. Written by a team of some of the best SQL Server experts in the industry, this comprehensive tutorial shows you how to navigate the vastly changed landscape of the SQL Server administration.